Keabsahan Akta Perjanjian Kredit Secara Daring yang Dibuat oleh Notaris Dalam Kondisi Pandemi Covid 19 - Miranti Verdiana (Notaire, 2021)
The validity of the credit agreement deed read out online is still subject to the provisions in Article 1320 BW. The validity of the Credit Agreement Deed that is read out online is still valid and valid and has perfect legal force. The perfect legal power in the credit agreement deed remains subject to and in accordance with the provisions of civil law BW and Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of a Notary. The validity of the Credit Agreement Deed that is read out online remains valid and valid and has perfect legal force, which is very important during the Covid 19 pandemic which has an impact on limiting access to face-to-face meetings. The legal basis for reading credit agreement deeds online is not required to read or does not need to meet, namely Article 16 paragraph (7) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public is an exclusion of the requirement for a notary to read the deed. credit agreement before the parties with the condition that the tappers have read it themselves, know it, and understand the contents of the deed to be made. The Credit Agreement Deed that is read out online carries legal risks for the parties and witnesses who appear, therefore the notary must authenticate the parties present online, if there is negligence in authenticating the parties and harming the party in the credit agreement deed, the notary is responsible civil liability, criminal responsibility and administrative responsibility. The research approach used in this research is a statutory approach and a conceptual approach.Keywords: Notary; Validity of the Credit Agreement Deed; Online.Keabsahaan akta perjanjian kredit yang dibacakan secara daring tetap tunduk pada ketentuan dalam Pasal 1320 BW. Keabsahan Akta Perjanjian Kredit Yang di Bacakan Secara Daring tetap sah dan berlaku serta mempunyai kekuatan hukum yang sempurna. Kekuataan hukum yang sempurna dalam akta perjanjian kredit tetap tunduk dan sesuai dengan ketentuan hukum perdata BW dan Undang-Undang Nomor 2 Tahun 2014 Tentang Perubahan Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris. Keabsahan Akta Perjanjian Kredit Yang di Bacakan Secara Daring tetap sah dan berlaku serta mempunyai kekuatan hukum yang sempurna sangat penting disaat pandemic covid 19 yang berdampak kepada dibatasinya akses untuk tatap muka secara langsung. Adapun dasar hukum pembacaan akta perjanjian kredit secara daring tidak diwajibkan dibacakan atau tidak perlu bertemu yaitu Pasal 16 ayat (7) Undang-Undang Nomor 2 Tahun 2014 Tentang Perubahan Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris merupakan Pasal pengecualiaan akan keharusan notaris membacakan akta perjanjian kredit dihadapan para pihak dengan syarat penghadap telah membacanya sendiri, mengetahuinya, serta memahami isi dari akta yang akan dibuat. Akta Perjanjian Kredit Yang di Bacakan Secara Daring membawa risiko hukum akan para pihak dan saksi yang menghadap oleh karena itu notaris harus melakukan autentifikasi para pihak yang hadir dalam daring, jika terjadi kelalaian dalam autentiikasi para pihak serta merugikan pihak dalam akta perjanjian kredit maka notaris bertanggung jawab perdata, tanggung jawab pidana dan tanggung jawab administratif. Pendekatan penelitian yang dipergunakan dalam penelitian ini adalah pendekatan perundang-undangan dan pendekatan konseptual.Kata Kunci: Notaris; Keabsahaan Akta Perjanjian Kredit; Daring.